Republic of Latvia : First and Second Reviews Under the Stand-By Arrangement and Request for Waiver of a Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper focuses on the Republic of Latvia's First and Second Reviews Under the Stand-By Arrangement and a Request for a Waiver of a Performance Criterion. Latvia has continued to follow prudent macroeconomic policies. All performance criteria under the IMF-supported program have been observed-except that the end-December 2001 fiscal deficit ceiling was exceeded by 0.2 percent of GDP because of local government budget overruns. Key financial sector indicators suggest no major vulnerabilities at this time. The current account deficit remains the main risk to Latvia's economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet